Do countries rely on the World Health Organization for translating research findings into clinical guidelines?: a case study - Noor, Ramadhani A.; Geldsetzer, Pascal; Bärnighausen, Till; Fawzi, Wafaie (Globalization and health, 2016)
The World Health Organization’s (WHO) antiretroviral therapy (ART) guidelines have generally been adopted rapidly and with high fidelity by countries in sub-Saharan Africa. Thus far, however, WHO has not published specific guidance on nutritional care and support for (non-pregnant) adults living with HIV despite a solid evidence base for some interventions. This offers an opportunity for a case study on whether national clinical guidelines in sub-Saharan Africa provide concrete recommendations in the face of limited guidance by WHO. This study, therefore, aims to determine if national HIV treatment guidelines in sub-Saharan Africa contain specific guidance on nutritional care and support for non-pregnant adults living with HIV.
Gesehen am 05.11.2020